Gender Inequality in Pakistan Caused by Domestic Factors and Conflict Resolving Based on CEDAW - Masitoh, Dewi; Pramesti, Firdha Ayu (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2020)
Gender inequality in Pakistan has been going for a long time from year to year. This can be evidenced by the results of a report from The Global Gender Gap Index in 2018 that was released by the World Economic Forum (WEF), Pakistan was the second worst country in the world in terms of gender equality, especially for the treatment of women, which ranks 148th out of 149 country. The aims of research are women’s participation is needed in a country by guaranteeing their freedom and welfare of state. If the lack of women's participation will be one of the roots of socio-economic and demographic problems that have been experienced by Pakistan until today. This research will use qualitative research methods, that emphasize the observation and understanding of a social phenomenon, where data is collected through secondary data and literature review. This research will use two theoretical frameworks, they are: Feminism and Human Rights. The main finding of the research was found in detail about how the problem of gender inequality in Pakistan; the reasons of gender inequality has been going on for a long time; and how about the conflict resolving from Pakistan Government based on International Law.